Biosimilars for Pediatric Patients With Inflammatory Bowel Disease: Pediatric Gastroenterology Clinical Practice Survey. Issue 5 (23rd February 2023) - Maltz, Ross M.; McClinchie, Madeline G.; Boyle, Brendan M.; McNicol, Megan; Morris, Grant A.; Crawford, Erin C.; Moses, Jonathan; Kim, Sandra C.
Abstract : Background: Biosimilars are biological agents that have been demonstrated to have similar safety and efficacy profiles as the originator. The objective of this study was to evaluate the perspectives of pediatric gastroenterologists in the United States (U.S.) toward biosimilar use and to explore factors that impact their comfort level with prescribing infliximab biosimilars. Methods: A cross-sectional survey was developed and distributed to pediatric gastroenterology physicians from the U.S. via a listserv (Pediatric gastroenterology Bulletin Board). Respondent's demographics were recorded. Using a 6-point Likert scale, the survey assessed the respondent's perceptions toward biosimilars and initiating switches from the originator to biosimilar agent along with factors impacting provider's comfort level. Fischer exact tests were used to detect statistically significant differences in responses for hypotheses of interest. Results: One hundred thirty-nine pediatric gastroenterologists completed the online survey (response rate 5.4%). Eighty-seven percent of respondents reported being comfortable prescribing infliximab biosimilars to anti-tumor necrosis factor naive patients, and 69% reported being comfortable doing a one-time switch if the patient was in clinical remission. Factors that negatively impacted a respondent's comfort level included respondents not practicing at an ImproveCareNow (ICN) center and managing less than 50 patients with inflammatory bowel diseases (IBD). Conclusions: Nearly 90% of pediatric gastroenterologists felt comfortable prescribing an infliximab biosimilar, and 70% felt comfortable with a one-time switch to the biosimilar if the patient was in clinical remission. Involvement in ICN a learning health system and caring for higher numbers of patients with IBD was associated with increased provider comfort with biosimilar use.